Gender Discourse in Islamic Family Law Between Text and Context - Dewi, Erna; Nur, Syamsiyah; Hasibuan, Badai; Ichsan, Muhammad (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Islam does not differentiate between men and women, skin color, or any other natural differences. In practice within society, women bear dual responsibilities such as cooking, washing, raising children, taking care of their husbands, and providing sexual services. In addition to earning a living and doing household chores, women also participate in activities. Women are viewed negatively if they neglect household responsibilities. Author's finding: that men only have one responsibility to earn a living, which certainly does not compare to women who do many things. This research uses literature study and qualitative field study. The findings and discussions include a review of qualitative research methods, literature studies, and field studies as a whole, or a combination of both. Furthermore, the data is analyzed using critical analysis techniques. The novelty in this research is